Toughened heat-resistant high-transparency modified polyester and preparation method thereof
By adding hydroxyethoxy aromatic derivative diol and flexible copolymerized modified monomer to the polyester, the glass transition temperature and thermal deformation temperature of PET are improved, and the high price of ABS materials and low glass transition temperature of domestic PET are solved. Problem, polyester materials with high transparency, toughness and heat resistance are achieved, suitable for replacing transparent ABS materials.
Patent Information
- Application Number
- CN202411692457.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-07
AI Technical Summary
The existing ABS materials are expensive, sensitive to solvents and cannot be recycled. The glass transition temperature of domestic PET is low, which limits its scope of application and cannot effectively replace transparent ABS materials.
Toughening heat-resistant high transparency modified polyester including terephthalic acid, ethylene glycol, hydroxyethoxy aromatic derivative diol, flexible copolymerized modified monomer, catalyst and stabilizer, through esterification and polycondensation The reaction increases the glass transition temperature and thermal deformation temperature, and combines the flexible copolymerization of the alkyl chain to improve the mobility of the molecular chain segments to avoid brittle problems.
It achieves high transparency, toughness and heat resistance, reduces production costs, is suitable for large-scale industrial production, can effectively replace transparent ABS materials, and improves the application range and cost-effectiveness of the materials.
Smart Images

Figure CN119264405A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to polyester and also to a method for preparing the polyester, belonging to the technical field of polymer materials. Background Art
[0002] Acrylonitrile-butadiene-styrene copolymer (ABS) is a very common thermoplastic. It is widely used in various fields such as consumer electronics, automotive parts, toys, and household appliances because of its advantages such as high mechanical strength, easy processing, and good electrical insulation. As my country continues to promote high-quality development, the demand for ABS in domestic downstream industries continues to grow, and the import volume of ABS has remained above one million tons in recent years. However, the price of ABS has remained high for a long time. It is sensitive to certain solvents (such as ketones and esters), cannot be recycled, and is not conducive to low-carbon life. Therefore, providing a new type of environmentally friendly material that is inexpensive and can replace ABS has broad application prospects.
[0003] Reference is made to the Chinese invention patent application with patent application number 202111631831.5, entitled "A polypropylene material with low warpage and low shrinkage performance and its preparation method" (application publication number CN114262481A), which discloses a polypropylene material with low warpage and low shrinkage performance and its preparation method, but the composition of the composite material is relatively complex, and it is necessary to add glass fiber, modified filler, shrinkage regulator, compatibilizer and other components; and reference is made to the Chinese invention patent application with patent application number 201610554244.3, entitled "A high-toughness PP composite material replacing ABS and its preparation method" (application publication number CN106009313A), which discloses a high-toughness PP composite material replacing ABS and its preparation method, and the PP composite material provided by the invention has a shrinkage rate and notched impact strength similar to those of ABS materials, and at the same time has higher toughness than ABS materials, which can make up for the poor toughness of ABS materials. However, both of the above two inventions require the addition of a large amount of glass fiber or talcum powder, which will greatly reduce the light transmittance of the material, which is not conducive to replacing transparent ABS materials.
[0004] Polyethylene terephthalate (PET) is a semi-crystalline thermoplastic with excellent performance. Because of the rigid benzene ring in its main chain, PET has high tensile strength, creep resistance, light transmittance and good wear resistance. In addition, PET has excellent tolerance to alcohols, aliphatic hydrocarbons, oils, greases and dilute acids, moderate tolerance to dilute alkalis, aromatic hydrocarbons and halogenated hydrocarbons, and excellent electrical insulation properties. PET is low-priced and recyclable, which is conducive to reducing environmental pollution and is expected to replace transparent ABS materials.
[0005] However, the glass transition temperature of PET is generally low (≤75℃), which seriously limits the application scope of PET and the export of domestic PET. At present, copolyesters with high glass transition temperature are basically monopolized by two international giants, Eastman in the United States and SK in South Korea. Technical protection measures are implemented in the whole process from raw material preparation to product processing. Therefore, the domestic market basically relies on imports from the United States and South Korea. A few domestic manufacturers are in the process of research and development and trial production, but they are still in an immature stage. Summary of the invention
[0006] The first technical problem to be solved by the present invention is to provide a toughened, heat-resistant and highly transparent modified polyester that can replace ABS in view of the above-mentioned technical status quo.
[0007] The second technical problem to be solved by the present invention is to provide a method for preparing a toughened, heat-resistant and highly transparent modified polyester that can replace ABS in view of the above-mentioned technical status quo.
[0008] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a toughened, heat-resistant and highly transparent modified polyester, characterized in that it includes the following components: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic hydrocarbon derivative diol, flexible copolymerization modification monomer, catalyst and stabilizer; the molar ratio of terephthalic acid to ethylene glycol is 1:1.1-1.8; the molar content of the hydroxyethoxy aromatic hydrocarbon derivative diol is 0.1%-10%; the molar content of the flexible copolymerization modification monomer is 0.1%-10%; the total amount of the catalyst added is 100-400ppm of the total mass of the polyester; the amount of the stabilizer added is 5-50ppm of the total mass of the polyester.
[0009] Preferably, the hydroxyethoxy aromatic hydrocarbon derivative diol has the following structure:
[0010]
[0011] Wherein R is any one of the following structural formulas:
[0012]
[0013] Preferably, the flexible copolymer modified monomer is at least one of adipic acid, 1,3-propylene glycol, butanediol and hexanediol.
[0014] Preferably, the catalyst is at least one of an antimony-based catalyst, a titanium-based catalyst, and a germanium-based catalyst.
[0015] Preferably, the stabilizer is a phosphorus stabilizer, and at least one of phosphoric acid, phosphorous acid, pyrophosphoric acid, ammonium phosphate, trimethyl phosphate, triphenyl phosphate, diphenyl phosphate, diphenyl phosphite, and ammonium phosphite may be used.
[0016] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing toughened heat-resistant and highly transparent modified polyester, comprising the following steps:
[0017] ① Esterification reaction: add terephthalic acid, ethylene glycol, hydroxyethoxy aromatic derivative diol, flexible copolymer modified monomer, catalyst and stabilizer into the reaction kettle, stir and heat to 230-250°C, control the pressure in the kettle to reach 300-380kPa, react for 1.5-3h, and when the esterification rate reaches 90-99%, release the pressure and discharge the esterification water;
[0018] ② Polycondensation reaction: gradually reduce the vacuum degree in the autoclave to less than 100 Pa, set the reaction temperature to 260-285°C, and react for 3-5 hours; discharge the material, cut into pellets, and obtain basic slices with a characteristic viscosity of 0.65-0.7 dL / g.
[0019] Compared with the prior art, the advantages of the present invention are: using hydroxyethoxy aromatic hydrocarbon derivative diol monomer as the third comonomer for heat resistance modification, and using a flexible comonomer as the fourth comonomer to achieve toughening modification, so that the prepared high glass transition temperature copolyester has both excellent heat resistance and toughness.
[0020] The introduction of highly reactive hydroxyethoxy aromatic derivative diols into traditional PET can increase the glass transition temperature and heat deformation temperature of PET, making its application range wider; the alkane chain flexible copolymerization modified monomer can improve the mobility of PET molecular segments, thereby increasing the crystallization rate of PET. At the same time, the addition of alkane chain flexible copolymerization modified monomer can also avoid the problem of brittleness of modified PET materials.
[0021] The copolymerization stage modification can make the hydroxyethoxy aromatic derivative diol and the flexible copolymerization modification monomer disperse more evenly, making the PET modification efficiency higher without affecting the transparency of the material, and can effectively replace the transparent ABS material. The addition of alkane chain flexible copolymerization modification monomer can improve the mobility of PET molecular segments, thereby improving the crystallization ability of PET. At the same time, the addition of alkane chain flexible copolymerization modification monomer can also avoid the problem of brittleness of modified PET materials.
[0022] The preparation method of the toughened heat-resistant and highly transparent polyester of the present invention is simple, the amount of additives added is small, and the polyester is suitable for large-scale industrial production, which can effectively reduce the cost and make the product highly cost-effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a test curve of glass transition temperature and melting point of Example 1.
[0024] Figure 2 This is a test curve diagram of glass transition temperature and melting point of Example 2.
[0025] Figure 3 This is a test curve of glass transition temperature and melting point of Example 3.
[0026] Figure 4 This is a test curve diagram of glass transition temperature and melting point of Example 4.
[0027] Figure 5 This is a test curve diagram of glass transition temperature and melting point of Example 5. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below with reference to the accompanying drawings.
[0029] Examples 1 to 5 are toughened heat-resistant transparent polyesters prepared by the method of the present invention. Comparative Example 1 is a common PET polyester material.
[0030] Example 1
[0031] The first stage of esterification reaction: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic hydrocarbon derivative diol (1), flexible copolymerization modification monomer, antimony catalyst, and phosphorus stabilizer are added to a reactor, the reactor is heated to 230-250°C, the pressure of the reactor is 300-380 kPa, the reaction time is 2.5 hours, the esterification rate reaches 98%, and the pressure is released. The molar ratio of PAT: EG: hydroxyethoxy aromatic hydrocarbon derivative diol (1): flexible copolymerization modification monomer is 1: 1.12: 0.04: 0.05, the amount of antimony catalyst added is 100 ppm of the total mass of the modified PET polyester, the amount of germanium catalyst added is 65 ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 20 ppm of the total mass of the modified PET polyester.
[0032] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 3.5h, and the toughened heat-resistant transparent polyester basic chips are obtained.
[0033] Example 2
[0034] The first stage of esterification reaction: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic hydrocarbon derivative diol (2), flexible copolymerization modification monomer, antimony catalyst, germanium catalyst, and phosphorus stabilizer are added to a reactor, the reactor is heated to 230-250°C, the pressure of the reactor is 300-380 kPa, the reaction time is 2 hours, the esterification rate reaches 96%, and the pressure is released. The molar ratio of PAT: EG: hydroxyethoxy aromatic hydrocarbon derivative diol (2): flexible copolymerization modification monomer is 1: 1.15: 0.1: 0.05, the amount of antimony catalyst added is 100 ppm of the total mass of the modified PET polyester, the amount of germanium catalyst added is 40 ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 30 ppm of the total mass of the modified PET polyester.
[0035] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 4.5h, and the toughened heat-resistant transparent polyester is obtained.
[0036] Example 3
[0037] The first stage of esterification reaction: add terephthalic acid, ethylene glycol, hydroxyethoxy aromatic derivative diol (3), flexible copolymerization modification monomer, germanium catalyst, and phosphorus stabilizer into a reactor, heat the reactor to 230-250°C, and the pressure of the reactor is 300-380 kPa. The reaction time is 2 hours, and the esterification rate reaches 97%, and the pressure is released. The molar ratio of PAT: EG: hydroxyethoxy aromatic derivative diol (3): flexible copolymerization modification monomer is 1: 1.10: 0.08: 0.06, the amount of antimony catalyst added is 100 ppm of the total mass of the modified PET polyester, the amount of germanium catalyst added is 40 ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 20 ppm of the total mass of the modified PET polyester.
[0038] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 4.5h, and the toughened heat-resistant transparent polyester is obtained.
[0039] Example 4
[0040] The first stage of esterification reaction: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic derivative diol (4), flexible copolymerization modification monomer, antimony catalyst, phosphorus stabilizer are added to a reactor, the reactor is heated to 230-250°C, the pressure of the reactor is 300-380 kPa, the reaction time is 2 hours, the esterification rate reaches 97%, and the pressure is released. The molar ratio of PAT: EG: hydroxyethoxy aromatic derivative diol (4): flexible copolymerization modification monomer is 1: 1.15: 0.05: 0.06, the amount of antimony catalyst added is 135 ppm of the total mass of the modified PET polyester, the amount of germanium catalyst added is 35 ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 25 ppm of the total mass of the modified PET polyester.
[0041] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 4 hours, and the toughened heat-resistant transparent polyester is obtained.
[0042] Example 5
[0043] The first stage of esterification reaction: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic hydrocarbon derivative diol (5), flexible copolymerization modification monomer, antimony catalyst, germanium catalyst, and phosphorus stabilizer are added to a reactor, the reactor is heated to 230-250°C, the pressure of the reactor is 300-380 kPa, the reaction time is 2.5 hours, the esterification rate reaches 98%, and the pressure is released. The molar ratio of PAT: EG: hydroxyethoxy aromatic hydrocarbon derivative diol (5): flexible copolymerization modification monomer is 1: 1.15: 0.05: 0.05, the amount of antimony catalyst added is 125 ppm of the total mass of the modified PET polyester, the amount of germanium catalyst added is 25 ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 25 ppm of the total mass of the modified PET polyester.
[0044] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 5 hours, and the toughened heat-resistant transparent polyester is obtained.
[0045] The corresponding hydroxyethoxy aromatic hydrocarbon derivative diols in each embodiment are as follows:
[0046]
[0047] Comparative Example 1
[0048] The first stage of esterification reaction: terephthalic acid, ethylene glycol, antimony catalyst, germanium catalyst and phosphorus stabilizer are added to the reactor, the reactor is heated to 230-250°C, the pressure of the reactor is 300-380 kPa, the reaction time is 2 hours, the esterification rate reaches 97%, and the pressure is released. The molar ratio of PAT:EG is 1:1.25, the amount of antimony catalyst added is 220ppm of the total mass of the modified PET polyester, and the amount of stabilizer added is 35ppm of the total mass of the modified PET polyester.
[0049] The second stage of polycondensation reaction: start the vacuum pump to gradually reduce the vacuum degree in the kettle to less than 100 Pa, the reaction temperature is 260-285°C, the reaction time is 3h, and the toughened heat-resistant transparent polyester is obtained.
[0050] Polyester general index test
[0051] The modified PET materials prepared in Examples 1 to 5 and Comparative Example 1 were subjected to conventional index testing, and the testing standards were as follows:
[0052] 1. The intrinsic viscosity is tested according to GB / T 17931-2018 6.4;
[0053] 2. The terminal carboxyl group is tested according to GB / T 17931-2018 6.8;
[0054] 3. The glass transition temperature is tested according to GB / T 19466.2-2004;
[0055] 4. Melting point is tested according to GB / T 19466.3-2004.
[0056] The test results are shown in Table 1:
[0057] Table 1 Modified PET conventional index test table
[0058]
[0059] Combined with the above table Figure 1 to Figure 5 It can be seen that the glass transition temperature of the toughened heat-resistant and highly transparent modified polyester provided by the present invention can be increased by about 10°C compared with ordinary polyester materials, while the melting point is reduced by 10 to 20°C. This is because the modified polyester uses a hydroxyethoxy aromatic hydrocarbon derivative diol monomer as the third comonomer for heat-resistant modification, and a flexible comonomer as the fourth comonomer, and the regularity of the polymer chain is reduced as a whole, resulting in a lower melting point. Therefore, the present invention not only increases the glass transition temperature of the polyester material, but also reduces the injection molding temperature during injection molding, which is more conducive to molding and energy saving.
[0060] Performance Testing
[0061] The modified PET materials prepared in Examples 1 to 5 and Comparative Example 1 were subjected to performance tests, and the test methods were as follows:
[0062] 1. Tensile strength and elongation at break are tested according to ISO527;
[0063] 2. Izod notched impact strength is tested according to ISO180;
[0064] 3. Heat deformation temperature is tested according to ISO75;
[0065] 4. Light transmittance is tested according to GB / T 2410-2008.
[0066] The test results are shown in Table 2:
[0067]
[0068] It can be seen from the above table that the notched impact strength and light transmittance of the toughened, heat-resistant, highly transparent modified polyester cantilever provided by the present invention are close to those of transparent ABS materials. The heat deformation temperature is slightly lower than that of transparent ABS materials, but is about 10°C higher than that of ordinary polyester materials. This is because the modified polyester uses a hydroxyethoxy aromatic hydrocarbon derivative diol monomer as the third comonomer for heat-resistant modification. The elongation at break is greater than 240%, which is more than 2.5 times that of conventional polyester materials and more than 5 times that of transparent ABS materials. This is because a flexible comonomer is used as the fourth comonomer in the modified polyester to achieve toughening modification. The above data show that the toughened, heat-resistant, highly transparent modified polyester prepared by the present invention has greatly improved toughness and heat resistance compared with conventional polyesters, and is expected to replace transparent ABS materials.
[0069] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A toughened, heat-resistant, highly transparent modified polyester, characterized in that The polyester comprises the following components: terephthalic acid, ethylene glycol, hydroxyethoxy aromatic hydrocarbon derivative diol, flexible copolymerization modification monomer, catalyst and stabilizer; the molar ratio of terephthalic acid to ethylene glycol is 1:1.1-1.8; the molar content of the hydroxyethoxy aromatic hydrocarbon derivative diol is 0.1%-10%; the molar content of the flexible copolymerization modification monomer is 0.1%-10%; the total amount of the catalyst added is 100-400ppm of the total mass of the polyester; the amount of the stabilizer added is 5-50ppm of the total mass of the polyester.
2. The toughened, heat-resistant, highly transparent modified polyester according to claim 1, characterized in that The hydroxyethoxy aromatic hydrocarbon derivative diol has the following structure: Wherein R is any one of the following structural formulas:
3. The toughened, heat-resistant, highly transparent modified polyester according to claim 1, characterized in that The flexible copolymer modified monomer is at least one of adipic acid, 1,3-propylene glycol, butanediol and hexanediol.
4. The toughened, heat-resistant, highly transparent modified polyester according to claim 1, characterized in that The catalyst is at least one of an antimony-based catalyst, a titanium-based catalyst, and a germanium-based catalyst.
5. The toughened, heat-resistant, highly transparent modified polyester according to claim 1, characterized in that The stabilizer is at least one of phosphoric acid, phosphorous acid, pyrophosphoric acid, ammonium phosphate, trimethyl phosphate, triphenyl phosphate, diphenyl phosphate, diphenyl phosphite, and ammonium phosphite.
6. A method for preparing the toughened, heat-resistant and highly transparent modified polyester according to any one of claims 1 to 5, comprising the following steps: ① Esterification reaction: add terephthalic acid, ethylene glycol, hydroxyethoxy aromatic derivative diol, flexible copolymer modified monomer, catalyst and stabilizer into the reaction kettle, stir and heat to 230-250°C, control the pressure in the kettle to reach 300-380kPa, react for 1.5-3h, and when the esterification rate reaches 90-99%, release the pressure and discharge the esterification water; ② Polycondensation reaction: gradually reduce the vacuum degree in the autoclave to less than 100 Pa, set the reaction temperature to 260-285°C, and react for 3-5 hours; discharge the material, cut into pellets, and obtain basic slices with a characteristic viscosity of 0.65-0.7 dL / g.
Citation Information
Patent Citations
ABS-substituting high-toughness PP composite material and preparation method thereof
CN106009313A
A high-toughness PP composite material as an alternative to ABS and its preparation method
CN106009313B
Polypropylene material with low warpage and low shrinkage performance and preparation method thereof
CN114262481A